EU Food Security Programme for the Caribbean Sanitary and Phytosanitary (SPS) Action in the Caribbean Region - Lawrence, Janet (2025)
In collaboration with CARICOM, CARIFORUM, Inter-American Institute for Cooperation on Agriculture (IICA), Caribbean Agricultural Research and Development Institute (CARDI), Caribbean Development Bank (CDB), Caribbean Private Sector Organisation (CPSO) and Food and Agriculture Organization of the United Nations (FAO)